16s rRNA Sequence Analysis and Ammonium Excretion Ability of Nitrogen Fixing Bacteria Isolated from Mineral Acid Soil - H. Hartono; Jaka Widada; Siti Kabirun (Indonesian Journal of Biotechnology, 2009)
Nitrogen fixing bacteria defined as bacteria which is capable to transform free nitrogen molecules into ammonium v (PCR). Nitrogenase activity of these selected isolates was measured using Acetylene Reduction Assay (ARA). The ability of these selected isolates in ammonium excretion was qualitatively and quantitavely measured using Nessler reagent and spectrophotometry method respectively. Taxonomic position of the selected bacteria were determined based on their 16S rRNA sequence analysis. Genetic diversity analysis of these 15 isolates of nitrogen fixing bacteria yield eight selected bacteria for subsequent analysis. Sequence of nifH gene from all of these selected bacteria were successfully amplified. Nitrogenase assay of these selected bacteria revealed 6 isolates with high nitrogen fixation capasity namely GMA3, GMA5, GMA6, GMA9, GMA12 AND GMA 13. Ammonium excretion analysis revealed 4 isolates which have remarkable ability of producing high level of ammonium namely GMA1, GMA3, GMA6, and GMA9. The 16S rRNA sequence analysis shown that isolates GMA3, GMA5, GMA11 and GMA12 had a close relationship with Brevibacillus formosus strain DSM 9885T, Flexibacter canadensis strain ISSDS-428, Rhizobium tropici strain rif 200849, and Azotobacter tropicalis strain RBS. Respectively, isolate GMA1 and GMA13 had a close relationship with Sthenotropphomonas sp. Strain MFC-C, while isolate GMA6 and GMA9 had a close relationship to Azotobacter vinelandii strain ISSDS-428. ', 'string'),(105, 'en_US', 'subject', 'nitrogen fixing bacteria, ammonium excretion, identification', 'string'),(105, 'en_US', 'sponsor', '', 'string'),(107, 'en_US', 'title', 'Effect of Probiotic Lactobacillus sp. Dad13 on Humoral Immune Response of Balb/C Mice Infected with Salmonella typhimurium', 'string'),(107, 'en_US', 'abstract', 'An indigenous strain of lactic acid bacterium (LAB) identified as Lactobacillus spp. Dad13 (Dad13), isolated from traditional fermented buffalo milk, was found to be potential as probiotic. The aim of this research was to study the effect of probiotic Dad13 on humoral immune response of Balb/C mice infected with Salmonella typhimurium. Thespecific objective was to find out the effect of different Dad13 consumption time (before and along with infection of S. typhimurium) on the humoral immune response of Balb/C mice. The experiment was conducted by in vivo trial on 20 males of Balb/C mice, age of 6-8 weeks, fed with AIN-93 standard diet. The mice were assigned into 4 groups. Each group received the following treatments, ie. Dad13 only, Dad13 before infection, Dad13 along with infection and Salmonella infection only. A volume of 100 μl Dad13 cell suspensions (1010 CFU/ml) were given by oral forced feeding daily for a week, at week 3 for group before infection and at week 4 for group of Dad13 only and Dad13 along with infection. Salmonella infection (109 CFU/ml) was given once orally at week 4 to all groups except group treated with Dad13 only. The humoral immune response of Balb/C mice was detected 2 weeks after infection by measuring the titers of IgG and IgA specific from serum and mucosal intestinal liquid samples using Enzyme-linked Immunosorbent Assay (ELISA) method. The result indicated that humoral immune response of Balb/C mice consuming Dad13 before and along with Salmonella infection were significantly different (p<0.05). Dad13 consumption along with Salmonella infection increased circulated IgG and IgA as well as secretory IgA. It can be concluded that Dad13 probiotic feeding along with infection increased humoral immune response more significantly compared to that before infection.